2009
DOI: 10.1111/j.1939-1676.2008.0267.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Characterization of a Feline Insulinoma

Abstract: Background: Insulinoma is an autonomous insulin-secreting islet cell neoplasm that is rarely diagnosed in cats. The clinical and pathological aspects of feline insulinoma have been described previously, but the molecular characteristics of these tumors have not been investigated.Objectives: The study objectives were to characterize peptide hormone production and determine expression of selected genes involved in glucose metabolism and insulin secretion in a feline insulinoma.Methods: Immunohistochemistry and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
5
14
0
Order By: Relevance
“…GCK activity in normal feline pancreas has yet to be confirmed. However, in a cat with a functional insulin-producing tumor and hypoglycemia, tumor GCK expression was nearly 17 times greater than normal pancreatic tissue from the same cat, suggesting a relationship between the magnitude of GCK expression and insulin secretion, similar to that observed in in vitro overexpression studies (7). Feline islets also express numerous other genes with roles in insulin signaling (67).…”
Section: Carnivore Hepatic Glucose-sensing Pathwayssupporting
confidence: 52%
See 2 more Smart Citations
“…GCK activity in normal feline pancreas has yet to be confirmed. However, in a cat with a functional insulin-producing tumor and hypoglycemia, tumor GCK expression was nearly 17 times greater than normal pancreatic tissue from the same cat, suggesting a relationship between the magnitude of GCK expression and insulin secretion, similar to that observed in in vitro overexpression studies (7). Feline islets also express numerous other genes with roles in insulin signaling (67).…”
Section: Carnivore Hepatic Glucose-sensing Pathwayssupporting
confidence: 52%
“…GCK mRNA has been detected in the feline pancreas (7, 35, 66) and in an insulin-producing pancreatic tumor from a cat (7). GCK activity in normal feline pancreas has yet to be confirmed.…”
Section: Carnivore Hepatic Glucose-sensing Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the glycogen-storage pathway is also very low in the cat (131) , then carbohydrates will be stored as lipids through de novo lipogenesis with the consistent associated pathophysiological complications, diabetes included (122) . In contrast to the situation observed in the liver, nutrient-sensing machinery seems to be present in feline pancreatic tissue, where the activity and expression of GK are comparable with those of other mammalian species (127) . Glucokinase in carnivorous species: the example of the dog.…”
Section: Rattus Norvegicusmentioning
confidence: 68%
“…Recent studies have shown that the feline liver does not express mRNA for GK [5] or GKRP [6], which suggests that reduced expression of genes involved in glucose-sensing is responsible for the low GK enzyme activity observed in early studies. Although GK mRNA expression has been documented in the feline pancreas [5,7], expression and activity of the feline pancreatic GK isoform has not been studied in depth. Given the central role of pancreatic GK as glucose-sensor for insulin-producing islet cells and the requirement for GK in normal glucose metabolism and insulin secretion, detailed knowledge about GK expression and function may improve understanding of feline carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%